The Role of Extracorporeal Membrane Oxygenation on Acute Respiratory Distress Syndrome - Dini Ardiyani; Zen Ahmad (HM Publisher, 2021)
Acute lung injury and acute respiratory distress syndrome are characterized by rapid-onset respiratory failure following a variety of direct and indirect insults to the parenchyma or vasculature of the lungs. Extracorporeal membrane oxygenation is a form of extracorporeal life support where an external artificial circulator carries venous blood from the patient to a gas exchange device (oxygenator) where blood becomes enriched with oxygen and has carbon dioxide removed. This blood then re-enters the patients circulation. The potential advantages of ECMO over conventional manajement may extend beyond its role in supporting patients with ARDS. ECMO may facilitate and enhance the application of lung-protective ventilation by minimizing ventilator-induced lung injury.